Acetic acid dressings: Finding the Holy Grail for infected wound management - Kapil S. Agrawal; Anup Vidyadhar Sarda; Raghav Shrotriya; Manoj Bachhav; Vinita Puri; Gita Nataraj (Indian Journal of Plastic Surgery)
Background: Wounds have since long, contributed majorly to the health-care burden. Infected long-standing non-healing wounds place many demands on the treating surgeon and are devastating for the patients physically, nutritionally, vocationally, financially, psychologically and socially. Acetic acid has long been included among agents used in the treatment of infected wounds. In this study, we have evaluated the use of acetic acid for topical application in the treatment of infected wounds. Materials and Methods: A total of 100 patients with infected wounds were treated with topical application of 1% acetic acid as dressing material after appropriate cleaning. A specimen of wound swab was collected before first application and further on days 3, 7, 10 and 14. Daily dressings of wounds were done similarly. Minimum inhibitory concentration (MIC) of acetic acid against various organisms isolated was determined. Results: The patients treated ranged between 9 and 60 years, with the mean age 33 years. Nearly 70% of patients were male. Aetiologies of wounds: infective 35, diabetic 25, trauma 20, burns 10, venous ulcers 5 and infected graft donor site 5. Various microorganisms isolated include Pseudomonas aeruginosa (40%), Staphylococcus aureus (2%), Acinetobacter (12%), Escherichia Coli (5%), Proteus mirabilis (3%), Klebsiella (18%), methicillin-resistant S. aureus (10%), Streptococcus (2%) and Enterococcus (1%), Citrobacter (1%). Few wounds (6%) also isolated fungi. About 28%, 64% and 8% of patients isolated no growth on culture after 7, 14 and 21 days, respectively. MIC of all isolated organisms was ≤0.5%. Conclusion: pH of the wound environment plays a pivotal role in wound healing. Acetic acid with concentration of 1% has shown to be efficacious against wide range of bacteria as well as fungi, simultaneously accelerating wound healing. Acetic acid is non-toxic, inexpensive, easily available and efficient topical agent for effective elimination of wound infections caused due to multi-drug resistant, large variety of bacteria and fungus.